Energy Consumption Behavior Analysis in the UAE Educational Buildings for Sustainable Economy: A Case Study of Ras Al Khaimah Schools - Hossin, Khaled; AlShehhi, Hessa (International Journal of Energy Economics and Policy, 2024)
Energy-saving in educational building has a significant contribution and a vital role in the economic and social development of nations. In this paper, the energy consumption of some educational buildings in the United Arab Emirates (UAE) are collected and analyzed. Four schools within the region of Ras Al Khaimah were selected to study their buildings’ energy consumption behavior. Key energy, economic and environmental parameters were calculated and investigated such as the total annual energy consumption, energy consumption per person, energy consumption per area, energy consumption by category (AC, lighting, other devices, etc.), energy cost, and the amount of greenhouse gas (GHG) emissions. A detailed energy audit was applied to one of the selected schools in order to identify the major areas of energy usage within the school, and to suggest the appropriate measures for potential energy and cost savings. Results revealed that total annual energy consumption of the investigated schools is very high with a range of 3700 - 3900 MWh. Significantly, in these hot climatic regions, AC systems alone accounts for over 80% of the overall annual energy consumption, standing out as the predominant energy consumers particularly during the summer months. The annual energy consumption per unit area was also excessive with values ranging from 200 to 500 kWh per m2. Total annual cost of energy was relatively substantial for all schools with values in the order of 1.2 - 1.5 million AED ($330,000 - $400,000). The negative effects of the CO2 emissions were estimated to be around 500 - 600 ton of CO2/year per a single school.